Linking words in Croatian academic writing - Vignjević, Jelena; Bašić, Tatjana (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
Academic writing is a skill that is mastered indirectly from the beginning of systematic education, and directly in academic education. One of the components of this skill is the harmonious use of linking or transition words by which the text in its wholeness, made up of interconnected parts, becomes clearer. When authoring academic papers, students often point out the use of linking words as the most demanding part of mastering the skill of academic writing. This paper presents the results of the analysis of usage of linking words in the students’ academic papers on the Faculty of Teacher Education, University of Zagreb. The corpus of texts for analysis consisted of fourteen academic papers by graduate students of a master level at the department of Preschool Teachers’ Education, created for the purpose of certifying knowledge for the course Croatian language in academic communication. The aim was to determine which linking words students most often use. The results of the analysis showed emphasized individual differences among students, when it comes to the choice and abundance of linking words, but also the predominantly correct inclusion of linking words in the text. The analysis showed that students use connectors more than modifiers. The analysis also brought a good insight into the frequency of the use of linking words in academic writing in the Croatian language.